Constructing identity: Experiences of Indonesian ESP teachers in a language institute - Mahendra, Aloisius Wisnu (English Language Teaching Educational Journal, 2020)
This study focuses on examining four Indonesian English for Specific Purposes (ESP) teachers’ experiences regarding their identity construction and negotiation in a language institute. Given the concern on an analytic framework by an adapted model of TESOL teacher identity, the teachers’ experiences were explored through life-history interview. The results revealed a complex process of transforming professional practices and constructing identities in relation to the struggles of becoming ESP teachers. The participants constructed ESP teacher identities through acquiring subject knowledge via professional development activities and building a sense of intrinsic fulfillment in becoming ESP teachers. However, the participants found challenge to cope with the students’ demands of learning ESP. Furthermore, a need to equip the ESP teachers with ESP skills in various subject knowledge areas became the participants’ concern in order to meet the students’ expectancy as well as to enhance their professional development.